2572. Decreased T-Cell Response, but Appropriate Antibody Production to Tetanus Vaccine Among HIV-Exposed Uninfected Infants in Botswana. (26th November 2018) - Smith, Christiana; Moraka, Natasha; Ibrahim, Maryanne; Moyo, Sikhulile; Mayondi, Gloria; Kammerer, Betsy; Leidner, Jean; Gaseitsiwe, Simani; Shapiro, Roger; Lockman, Shahin; Weinberg, Adriana
Abstract: Background: In Botswana, more than 10% of HIV-exposed, uninfected infants (HEU) are hospitalized or die in the first 6 months of life, largely due to infectious causes. Vaccine responses can act as a marker of the immune response to infectious antigens. Previous studies of vaccine responses in HEU have had conflicting results. We compared T-cell responses to tetanus and purified protein derivative (PPD), and antibody titers to tetanus, between HEU and HIV-unexposed infants (HUU). Methods: A total of 443 HIV-infected and 451 HIV-uninfected mothers and their 453 HEU/457 HUU live-born infants were followed from pregnancy/delivery through 24 months postpartum in a prospective observational study in Botswana ("Tshipidi"). T-cell expression of interferon (IFN)-γ and interleukin (IL)-2 were measured at 6 months using FluoroSpot after stimulation with tetanus toxoid or PPD. Quantitative tetanus toxoid IgG was measured in plasma at 18 months using ELISA. Mean spot-forming units (sfu) per 10 5 cells and geometric mean antibody titers were compared between HEU and HUU infants who had received 3 doses of tetanus and 1 dose of Bacille Calmette–Guérin (BCG) vaccines by 6 months, and 3 or 4 doses of tetanus vaccine by 18 months. Results. Peripheral blood mononuclear cells were available at 6 months for 63 HEU and 18 HUU. Plasma was available at 18 months for 39 HEU and 42 HUU. HEU infants had significantly lower IL-2 expression after tetanus stimulation than HUU infants (4.4 vs. 16.1 sfu/10 5 cells, P = 0.004; figure), but no difference in IFNγ expression. There were no differences in T-cell responses to PPD between HEU and HUU. There were no differences in tetanus geometric mean antibody titers between HEU and HUU. Conclusion. In this cohort of infants from Botswana, we found decreased T-cell responses, but not antibody responses, to tetanus toxoid and no differences in T-cell responses to PPD. Cell-mediated immune defects may play a greater role than humoral immune defects in the increased susceptibility to infection among HEU. BCG vaccine produces robust T-helper 1 responses, which may overcome cell-mediated immune defects in HEU. Disclosures: All authors: No reported disclosures.